Protocolo de intervención psicosocial en pacientes oncológicos sometidos a cirugía torácica - Bringas, Sara; Krikorian, Alicia; Hernando, Florentino; Rodríguez, Olga; Jarabo, José Ramón; Fernández, Elena; Gómez, Ana María; Calatayud, Joaquín; Balibrea, José Luis; Olivares, Mª Eugenia (Psicooncología, 2006)
At present, lung cancer is the most common cause of death worldwide from cancer in men and the second among women. Moreover, lung cancer shows an increasing rate of incidence and mortality among the world’s population. Surgical resection, if feasible, is the treatment of choice. However, surgical treatment can cause a great amount stress, both for patients and their families. To reduce psychological and emotional distress and improving quality of life, psychosocial evaluation and intervention should begin prior to the surgical procedure and continue through the postsurgical period. In this paper, the psychosocial evaluation and intervention protocol developed in the Thoracic Surgery Unit of the Hospital Clínico San Carlos of Madrid is presented.
Keywords: Lung cancer; Surgical treatment; Psychosocial evaluation; Psychosocial intervention; Quality of life